b - Abascal, Julio; Barbosa, Simone; Fetter, Mirko; Gross, Tom.; Palanque, Philippe; Winckler, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The four-volume set LNCS 9296-9299 constitutes the refereed proceedings of the 15th IFIP TC13 International Conference on Human-Computer Interaction, INTERACT 2015, held in Bamberg, Germany, in September 2015. The 74 full and short papers and 4 organizational overviews, 2 panels, 6 tutorials, and 11 workshops included in the fourth volume are organized in topical sections on tangible and tactile interaction; tools for design; touch and haptic; user and task modelling; visualization; visualization 3D; visualization in virtual spaces; wearable computing; demonstrations; and interactive posters.
Tangible and tactile interaction -- Tools for design -- Touch and haptic -- User and task modelling.-Visualization -- Visualization 3D -- Visualization in virtual spaces -- Wearable computing -- Demonstrations -- Interactive Posters.
Keywords: Computer science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).